Settlement-time behavior of peat ground and applicability of conventional predicting methods - HAYASHI, Hirochika; YAMAZOE, Nobutaka; TANAKA, Hiroyuki; MITACHI, Toshiyuki (Japanese Geotechnical Journal, 2011)
Prediction of the settlement-time behavior is one of the most important subject when the construction works are performed on peat ground since the order of the settlements is very large and they continue for a long period of time. In this paper, the following topics which are considered to be obstacles to perform accurate prediction of the settlement-time behavior of the peat ground are investigated: evaluation of the in situ permeability, reduction of the thickness of the objective layers caused by consolidation, additional vertical deformations accompanied with shear deformations and stress dependency of the coefficient of consolidation (cv). One and two dimensional soil-water coupled elasto-plastic FE analyses base on infinitesimal/finite deformation theory are carried out for two test embankments constructed on the peat ground having quite different cv values to identify which subjects described above mainly governs the settlement behavior. Settlement-time behavior is also investigated with a series of one-dimensional analyses by changing the rate of reduction of cv with consolidation stress change. Applicability of two conventional settlement prediction methods, an empirically established practical method and a method based on Terzaghi theory, is discussed based on the analytical results and observation, and important points to remember on application of the methods are elucidated.